On the Accuracy of Clinical Insertion Angle Predictions With a Surgical Planning Platform for Cochlear Implantation. Issue 9 (October 2021) - Avallone, Emilio; Lenarz, Thomas; Timm, Max E.
Abstract : Hypothesis: Various studies over the last few decades have shown that the cochlea is not a uniform structure, but that its size and shape may vary quite substantially in between subjects. The surgical planning platform enables the user to quickly approximate the size of a cochlea within clinical imaging data by measuring the basal cochlear diameters A and B. It also allows for contact specific insertion angle predictions for MED-EL cochlear implant electrode arrays based on this individual anatomy approximation. The proposed, retrospective study was performed to evaluate the accuracy of these predictions. Methods: Preoperative CBCT scans of N = 91 MED-EL cochlear implant patients with different types of FLEX electrode arrays (flexible, thin, and straight arrays) were evaluated using a planning module. Both the initial version (based on an equation proposed by Escudé et al.) as well as a novel, recently proposed approach (called elliptic-circular approximation) was employed. All predictions were then compared to the actual insertion angles which were derived from postoperative CBCT images of the same patient. Results: Most prediction deviations of the investigated cases stayed below 45deg for all electrode arrays and both prediction methods. In general, prediction deviations increased from base to apex were found to be larger for longer electrode arrays. Hardly any significant differences between the two prediction methods were observed. However, particularly large deviations were found for the Escudé method and could be substantially deceased with the updated elliptic-circular approximation approach. Conclusions: The new platform version with its updated prediction module allows to reliably predict insertion angles even for cochlear anatomies with slightly unusual features and shapes.